ANALYSIS OF THE ANTI-CORRUPTION STRATEGY-2030 OF UZBEKISTAN - Eshboev Sharafiddin Alisher ugli (Scholars Digest Publishing, 2024)
This article analyzes the national anti-corruption program of the Republic of Uzbekistan until 2030, and also shows the actions taken to prevent and reduce corruption in our country. In recent years, corruption has become a big problem for many countries.
Keywords: corruption, public service, openness index, reforms, strategy.